2015
DOI: 10.3906/vet-1306-30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics, oligosaccharides, and berberine combinationson growth performance of pigs

Abstract: Materials and methods MaterialsProbiotics contained Bacillus subtilis, Lactobacillus casei, and Pichia anomala (formerly named Hansenula anomala) at a ratio of 2:3:2 as in the previous report from our laboratory (6). The microbial counts in the combinations were 7 × 10 9 colony forming units per gram (CFU/g). Oligosaccharides (98% effective concentration, Alltech Co., Ltd., Beijing, China), berberine (98% effective concentration, Shanghai Yisha Biological Technology Co., Ltd., Shanghai, China), and aureomycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Others have reported similar observations previously (Fan et al, 2015;Wang et al, 2012). The content of albumin and globin reflect the digestibility and utilization of protein.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Others have reported similar observations previously (Fan et al, 2015;Wang et al, 2012). The content of albumin and globin reflect the digestibility and utilization of protein.…”
Section: Discussionsupporting
confidence: 67%
“…Many studies have shown that synbiotics are good substitutes for antibiotics in feed (Estrada, Drew, & Van Kessel, 2001;Guerra-Ordaz et al, 2013). The reasons are that probiotics and prebiotics can synergistically promote growth of animals as well as improve their resistance to infections by equilibrating intestinal microbiota and stimulating the immune system (Fan, Chang, Yin, Wang, & Dang, 2015;Guerra-Ordaz et al, 2013;Liu et al, 2016). A previous study suggested that synbiotics containing L. plantarum and lactulose increased ADG in weaned pigs (Guerra-Ordaz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that LJ could improve the development of the jejunum and ileum. Probiotics can also enhance the growth performance by improving the activities of different digestive enzymes ( Timmerman et al, 2006 ; Fan et al, 2015 ). Similarly, the present study showed considerably higher activities of trypsin in the jejunum and lipase in both the jejunum and ileum relative to those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the swine industry has been trying to make some dietary mixtures using enzymes and/or probiotics to have their beneficial effects all together. There are some studies to verify the effects of dietary mixtures of enzymes and probiotics [2,10,23,24], but the experimental evidence for their positive or negative effects in pig diets is limited. Therefore, the objective of this study was to investigate effects of dietary mixture of protease and probiotics on growth performance, blood constituents, and carcass characteristics of growing-finishing pigs.…”
Section: Introductionmentioning
confidence: 99%